Marine Spatial Planning in a Transboundary Context: Linking Baja California with California's Network of Marine Protected Areas - Arafeh-Dalmau, Nur; Torres-Moye, Guillermo; Seingier, Georges; Montaño-Moctezuma, Gabriela; Micheli, Fiorenza (Frontiers in Marine Science, 2017)
It is acknowledged that an effective path to globally protect marine ecosystems is through the establishment of eco-regional scale networks of MPAs spanning across national frontiers. In this work we aimed to plan for regionally feasible networks of MPAs that can be ecologically linked with an existing one in a transboundary context. We illustrate our exercise in the Ensendense eco-region, a shared marine ecosystem between the south of California, United States of America (USA), and the north of Baja California, Mexico; where conservation actions differ across the border. In the USA, California recently established a network of MPAs through the Marine Life Protection Act (MLPA), while in Mexico: Baja California lacks a network of MPAs or a marine spatial planning effort to establish it. We generated four different scenarios with Marxan by integrating different ecological, social, and management considerations (habitat representation, opportunity costs, habitat condition, and enforcement costs). To do so, we characterized and collected biophysical and socio-economic information for Baja California and developed novel approaches to quantify and incorporate some of these considerations. We were able to design feasible networks of MPAs in Baja California that are ecologically linked with California’s network (met between 78.5 and 84.4% of the MLPA guidelines) and that would represent a low cost for fishers and aquaculture investors. We found that when multiple considerations are integrated more priority areas for conservation emerge. For our region, human distribution presents a strong gradient from north to south and resulted to be an important factor for the spatial arrangement of the priority areas. This work shows how, despite the constraints of a data-poor area, the available conservation principles, mapping, and planning tools can still be used to generate spatial conservation plans in a transboundary context.